Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Di Karoseri PT. Adhikarisma Pratama - Ade Siantry; Dhian Tyas Untari; Andrian Andrian (Universitas 45 Surabaya, 2024)
This research aims to determine the influence of product quality, price and service quality on customer loyalty at PT Karoseri. Adhicharism Pratama. This type of research is quantitative. The population in this study is unknown. The sampling technique uses Non-Probability Sampling using the Saturated Sample technique. The sample in this study amounted to 61 respondents. Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Multiple Linear Regression analysis. The research subjects were PT Karoseri consumers. Adhicharism Pratama. The results of this research show that the variables of product quality, price and service quality partially and simultaneously have a significant effect and have a positive influence on the customer loyalty variable.